The evolution of canaliculate rudists in the light of a new canaliculate polyconitid rudist from the Albian of the Central Pacific. (31st January 2014) - Sano, Shin‐Ichi; Iba, Yasuhiro; Skelton, Peter W.; Masse, Jean‐Pierre; Aguilar, Yolanda M.; Kase, Tomoki; Jagt, John
Abstract A new polyconitid rudist, Magallanesia canaliculata gen. et sp. nov., of probably late Albian age, is described from the Pulangbato area, central Cebu Island, the Philippines in the western Central Pacific and Takuyo‐Daini Seamount, now located in the Northwest Pacific. It is similar to Praecaprotina Yabe and Nagao, 1926, a Japanese–Central Pacific endemic genus of late Aptian – early Albian age, but differs in having canals that developed by partitioning of the large ectomyophoral cavity in the posterior part of the left valve. Its discovery strengthens the evidence for Pacific endemism in Albian times. Several other clades of canaliculate rudists flourished or evolved at the same time in different regions of the Tethyan Realm, suggesting the presence of common global biological and/or environmental factors stimulating the evolution of the canals despite such endemism. Furthermore, the finding of a canaliculate polyconitid provides evidence in favour of the evolutionary hypothesis of a polyconitid origin for the Late Cretaceous canaliculate rudist family Plagioptychidae Douvillé, 1888.